2011
DOI: 10.1007/s00417-011-1824-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of dilated retinal arteriolar caliber with early age-related macular degeneration: the Handan Eye Study

Abstract: Dilated retinal arteriolar caliber is associated with early AMD and soft distinct drusen in this population. We found no significant associations between CRAE and other characteristics of the retina related to AMD or between retinal venal caliber and early AMD. More research is needed to determine whether the difference between these results and those previously published stem from the rural living conditions of the participants or other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Although some studies found no association between retinal arteriolar diameter and choroidal neovascular activity, subretinal fluid, or CMT [33][34][35][36] , the Handan Eye Study [37] reported a relationship between dilated retinal arteriolar caliber and early AMD. Nevertheless, we did not confirm this possibility clinically in noninjected eyes during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies found no association between retinal arteriolar diameter and choroidal neovascular activity, subretinal fluid, or CMT [33][34][35][36] , the Handan Eye Study [37] reported a relationship between dilated retinal arteriolar caliber and early AMD. Nevertheless, we did not confirm this possibility clinically in noninjected eyes during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, several studies have also examined the association between retinal vascular caliber and age-related macular degeneration (AMD) [114,115,116]. The results from these studies have been inconsistent.…”
Section: Retinal Vascular Caliber and Ocular Diseasesmentioning
confidence: 99%
“…Data from the Singapore Malay Eye Study revealed that wider venular caliber was independently associated with early AMD, whereas no relationship was found between retinal arteriolar caliber and AMD [114]. The Handan Eye Study showed that wider retinal arteriolar caliber was related to early AMD and venular caliber was not related to AMD [115]. In contrast to both these studies, cross-sectional data from the Beaver Dam Eye Study showed no association between retinal vascular calibers and AMD [116].…”
Section: Retinal Vascular Caliber and Ocular Diseasesmentioning
confidence: 99%
“…11 To date, several population-based studies have examined the relationship between retinal vascular caliber and AMD in Caucasian populations, [12][13][14] and some Asian, including Chinese and Malay, populations. [15][16][17] With respect to Caucasian studies, longitudinal data from the Beaver Dam Eye Study and the Blue Mountains Eye Study found no association between retinal vascular caliber and AMD. 12,14 In contrast, the Rotterdam Study found a borderline association between smaller arteriolar caliber and AMD in persons older than 75 years.…”
Section: Introductionmentioning
confidence: 97%